Asymptotic representations of solutions of essentially nonlinear two-dimensional systems of ordinary differential equations - Evtukhov, V. M.; Vladova, E. S.; Евтухов, В. М.; Владова, E. С.; Евтухов, В. М.; Владова, E. С. (Institute of Mathematics, NAS of Ukraine, 2009)
We establish asymptotic representations for one class of solutions of two-dimensional systems of ordinary differential equations that are more general than systems of the Emden–Fowler type.